THE EXEMPLARY STORY OF PROPHET YUSUF AS IN AVOIDING ZINA THROUGH FAKHRUDDIN AL-RAZI’S LENS - Fadhli, Muhajirul; Nurkhalis, Nurkhalis (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Promiscuity between men and women becoming a popular topic in modern society has resulted in the increasing pregnancy and abortion cases among the youths. This condition may lead to disruption in the order of the society. This article focuses on Imam Fakhruddin Al-Razi’s perspective in his book Mafatih Al-Ghaib about Prophet Yusuf (AS) resistance to Zulaikha’s seduction mentioned in the Quran. This study uses a qualitative approach with textual analysis as the method. The researcher conducted an in-depth analysis of the exemplary values reflected in the Prophet Yusuf’s (AS) behaviours in abstaining from immoral acts. The finding of the study shows that the Prophet Yusuf (AS) did three major acts in refraining himself from committing zina (adultery). First, mentioning the name of Allah SWT as a way to remember God's presence regardless of when and where. Secondly, resisting with all his might and even overcoming formidable obstacles, and finally, migrating to a new place. Prophet Yusuf (AS) is a religious figure who embodies noble and exemplary values that can establish a more moral and ethical society.